Determination of the Granulosa Cell-Specific Endothelin Receptor A Deletion on Ovarian Function - Jong-Ki Cho (The Korean Society of Animal Reproduction and Biotechnology, 2014)
Endothelin 2 (EDN2) induces follicular rupture by constricting periovulatory follicles. In this study, it was investigated the mechanisms of EDN2 action on follicular rupture with respect of receptor using the conditionally granulosa cell specific EDN2 receptor type A (ETa) KO mice (gcETaKO; ETaflox/-?Amhr2Cre). It was generated the gcETaKO mice by breeding with ETaflox/- mice after mono-alleic ETa knockout by ZP3Cre and Amhr2Cre mice. Fertility, ovulation and maturation rates of ovulated oocytes after super ovulation were investigated in the gcETaKO mice compared with wild-type mice (ETaflox/flox and ETaflox/-) as a control group. In the gcETaKO mice, normal fertility after breeding with male mice was shown compared with wild-type mice. And, there was no significant differences in ovulation rates after super ovulation, however its maturation rates was lower than that of wild type mice. These findings show that EDN2 in follicular rupture for ovulation is related with an other ETa not in granulosa cells. Further studies are needed to investigate how EDN2 is acted in ovarian follicular rupture for ovulation.